Asuhan Keperawatan Jiwa Pada Pasien Dengan Halusinasi Pendengaran Di Wisma Flamboyan Rsj Prof. Dr Hb . Saanin Padang 2026 - Rissa Aprilia Putri; Ramaita Ramaita; Dwi Happy Anggia Sari; Vivi Yuderna (CV. ITTC INDONESIA, 2026)
Hallucinations are a perceptual disorder in which the client perceives something that is not actually happening, resulting in a loss of self-control, where the client experiences panic and behavior is controlled by hallucinations. The purpose of this study is to explain the application of psychiatric nursing care to patients experiencing auditory and visual hallucinations at Wisma Flamboyan. The method used is a case study with a nursing process approach that includes assessment, diagnosis, planning, implementation, and evaluation. The results of the assessment indicate that the client experienced signs and symptoms of hallucinations, namely hearing whispers, anxiety, and talking to himself. The main nursing diagnosis is hallucinations with an additional diagnosis of self-care deficit. After receiving nursing care, the client showed progress in overcoming his nursing problems and was able to control hallucinations independently by applying implementation strategies (SP 1-4). The interventions implemented included reprimanding exercises, regular medication adherence, conversations, and carrying out scheduled daily activities. These results indicate that the application of SP is effective in helping clients manage hallucinations and increasing independence in self-care. This study is expected to increase public understanding and awareness of the importance of maintaining mental health in order to achieve maximum well-being.